Microbial Decolorization of Textile Dye Effluent - Devassy, Bella (My University, 2010)
Three aerobic mixed bacterial cultures SKB-I, SKB-II and Con3 were developed and screened for consistent decolorization efficiency using six selected azo dyes viz: Direct Red 28, Direct Red 7, Acid Blue 113, Direct Blue 53, Reactive Orange 107 & Reactive Red 120 at a concentration of 10 mg/L. Among the three, SKB-II was the most efficient decolorizer as it decolorized four out of the six selected azo dyes. Dyes: Direct Red 28, Direct Red 7, Acid Blue 113 and Direct Blue 5. Effect of various concentrations of medium components (starch: 0.65 and 1.3 g/L along with NaCl: 4, 2 and 0%) on the efficiency of mixed culture SKB-II to decolorize was studied and it was observed that best decolorization was achieved with 1.3 g/L starch and 4% NaCl. Among the fifftythree pure bacterial strains, five distinct bacterial strains (isolated from mixed culture) decolorized Direct Red 28 dye and were identified by 16 srDNA analysis as Bacillus sp. Studies were conducted to evaluate the efficiency of mixed culture to decolorize four azo dyes (Direct Red 28, Direct Red 7, Direct Blue 53 & Acid Blue 113 at a higher concentration from 10-100 mg/L individually and as a mixture (two and four dyes) and to decolorize real raw untreated effluent collected from various dyeing industries and local dyeing houses. In both cases, it was observed that decolorization efficiency and growth (as protein) of the mixed culture SKB-II was observed to be decreasing with increasing dye concentration and high effluent concentration. Optimization of parameters was carried out in glass column bioreactor with plastic clips and marble chips as immobilization support material with hydraulic retention time (11, 7.3 and 5.5 hrs for plastic clips and 8.16, 5.4 and 4 hrs for marble chips) across two aeration rates (0.4 and 0.6 mmoles/min.). By comparing the initial and final absorbance, values of the dye (Direct Red 28 at a concentration 10mg/L in BHB medium) after treatment through the bioreactor maximum decolorization was observed with marble chips as matrix at an aeration rate of 0.6 mmoles/min. and hydraulic retention time of 8.16hrs. And therefore, the real raw untreated effluent (5%) was also treated at the same parameter in the bioreactor.
Ph.D.(DBT)
Keywords: Azo dyes; Bacteria; Decolorization; industrial effluent